Preparation method of hydrolysis-resistant magnesium oxide used in organic silica gel

By forming a magnesium-aluminum spinel protective layer on the surface of magnesium oxide and hydrophobic coating with silane coupling agent, the problem of magnesium oxide being easily dehydrated in organic silicone is solved, which significantly improves its stability and hydrolysis resistance and enhances the performance of organic silicone.

CN119708884APending Publication Date: 2025-03-28FOSHAN SANSHUI JINGE NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411900083.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When used in organic silicone, magnesium oxide is highly hygroscopic, and it is prone to dehydration under high temperature and high humidity conditions, resulting in insufficient stability and weather resistance, affecting the long-term performance of the material.

Method used

By forming a dense protective layer of magnesium aluminum spinel on the surface of magnesium oxide and combining with hydrophobic coating of silane coupling agent, the physicochemical stability of magnesium oxide is enhanced and the influence of moisture is isolated.

Benefits of technology

It significantly improves the stability and hydrolysis resistance of magnesium oxide in high temperature and high humidity environments, enhances its compatibility and filling performance with silicone matrix, and improves the thermal conductivity and comprehensive performance of silicone gel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005202915390000061
    Figure BDA0005202915390000061
  • Figure BDA0005202915390000071
    Figure BDA0005202915390000071
Patent Text Reader

Abstract

The invention relates to a preparation method of hydrolysis-resistant magnesium oxide used in organic silica gel. The method comprises the following four main steps: firstly, mixing magnesium oxide with an aluminate solution through a high-speed mixer to obtain primary coated powder; secondly, mixing aluminum oxide with the primary coating powder to form secondary coating powder; then, carrying out high-temperature calcination on the secondary coated powder to obtain a high-temperature calcined product; and finally, carrying out surface modification on the calcined product by using a silane coupling agent to obtain the final hydrolysis-resistant magnesium oxide. According to the method, a magnesium aluminate spinel protective layer is formed, so that the hydrolysis resistance of magnesium oxide in organic silica gel is remarkably improved, and a deliquescence reaction in a high-temperature and high-humidity environment is effectively prevented. Meanwhile, the silane coupling agent is used for surface modification, so that the hydrophobicity of the magnesium oxide is enhanced, the compatibility of the magnesium oxide and an organic silicon matrix is improved, and the application effect of the magnesium oxide in the organic silica gel is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of magnesium oxide powder coating and organic silica gel materials, and particularly relates to a method for preparing hydrolysis-resistant magnesium oxide used in organic silica gel. Background Art

[0002] Magnesium oxide is an ionic compound that is a white solid at room temperature. It mainly exists in nature in the form of periclase. Different types of magnesium oxide can also be obtained through various preparation methods such as calcination, precipitation, sol-gel and acid-base leaching, including ordinary magnesium oxide, light magnesium oxide, heavy magnesium oxide, light-burned magnesium oxide and heavy-burned magnesium oxide. These diverse forms of magnesium oxide exhibit excellent thermal stability, chemical inertness, electrical insulation, wear resistance and high thermal conductivity, and are therefore widely used in many fields such as refractory materials, electronic appliances, pharmaceutical manufacturing, chemical raw materials and ceramics.

[0003] Due to its higher thermal conductivity than aluminum oxide, magnesium oxide has a theoretical thermal conductivity of 30W / mk-60W / mk, making it one of the ideal fillers in the field of organic silicone in the chemical industry, which can effectively improve the thermal conductivity of the material. Although magnesium oxide has excellent thermal conductivity, it has not yet been widely used in the field of organic silicone. This is because magnesium oxide has strong hygroscopicity, especially when the particle size of magnesium oxide is small or the specific surface area is large, its hygroscopicity will be significantly enhanced. Excessive hygroscopicity will cause magnesium oxide to deliquesce more violently under high temperature and high humidity conditions, gradually turning into magnesium hydroxide, thereby reducing its purity and stability.

[0004] The hygroscopic properties of magnesium oxide make it possible for magnesium oxide to gradually expand, crack and powder in a high temperature, high humidity and weather-resistant environment after being used as a filler in organic silicone, which seriously affects the long-term stability and weather resistance of organic silicone. Therefore, in order to enable magnesium oxide to be used in organic silicone on a large scale, a method is urgently needed to ensure that magnesium oxide can remain stable and not hydrolyzed under high temperature and high humidity conditions, so as to improve its weather resistance and enable it to be widely used in high-performance organic silicone materials. Summary of the invention

[0005] Based on the problem of strong hygroscopicity and easy hydrolysis of magnesium oxide when used in organic silica gel, the purpose of the present invention is to provide a method for preparing hydrolysis-resistant magnesium oxide for use in organic silica gel, so that it has stronger stability and hydrolysis resistance in a high temperature and high humidity environment. The method is achieved in the following manner: under the synergistic effect of aluminate, fine-grained aluminum oxide is used to react with the surface of magnesium oxide at high temperature to form a tight aluminum oxide coating layer on the surface of magnesium oxide; then, organic coating is performed by a silane coupling agent, so that the coated magnesium oxide not only has excellent physical and chemical stability, but also can effectively isolate the influence of moisture on magnesium oxide.

[0006] The technical points and principles of the hydrolysis-resistant magnesium oxide used in organic silica gel prepared by the present invention are as follows: (1) Formation of magnesium-aluminum spinel and improvement of hydrolysis resistance: The present invention is based on the principle that aluminum oxide and magnesium oxide can diffuse with each other under high temperature conditions to form magnesium-aluminum spinel. Aluminum oxide of appropriate particle size is coated on the surface of magnesium oxide, and after high-temperature calcination treatment, a dense protective layer of magnesium-aluminum spinel is formed. The magnesium-aluminum spinel has strong chemical stability and can effectively block the penetration of water and prevent magnesium oxide from undergoing deliquescence reaction with water, thereby significantly improving the hydrolysis resistance of magnesium oxide. By regulating the amount of aluminum oxide added and the particle size, the thickness and density of the magnesium-aluminum spinel protective layer can be optimized, thereby improving the hydrolysis resistance of magnesium oxide. (2) Surface modification of silane coupling agent: In order to further improve the hydrolysis resistance and compatibility of magnesium oxide with the organosilicon matrix, the present invention introduces a silane coupling agent for surface modification. The silane coupling agent can form a hydrophobic film on the surface of magnesium oxide, significantly reducing the hydrophilicity of the surface of magnesium oxide, thereby reducing the adsorption and contact of water, and further improving its hydrolysis resistance. The modification of the silane coupling agent can also improve the compatibility of magnesium oxide with the organosilicon matrix, enhance its dispersibility and filling properties in the organosilicon material, and is conducive to the preparation of high-performance organosilicon products. (3) Surface modification of silane coupling agent: In order to further improve the hydrolysis resistance and compatibility of magnesium oxide with the organosilicon matrix, the present invention introduces a silane coupling agent for surface modification. The silane coupling agent can form a hydrophobic film on the surface of magnesium oxide, significantly reducing the hydrophilicity of the surface of magnesium oxide, thereby reducing the adsorption and contact of water, and further improving its hydrolysis resistance. The modification of the silane coupling agent can also improve the compatibility of magnesium oxide with the organosilicon matrix, enhance its dispersibility and filling properties in the organosilicon material, and is conducive to the preparation of high-performance organosilicon products.

[0007] The present invention provides a method for preparing hydrolysis-resistant magnesium oxide for use in organic silica gel, and the specific steps are as follows: Step 1: Place magnesium oxide in a high-speed mixer, take a certain amount of heated and dissolved aluminate in an auxiliary material spraying device, spray the auxiliary material at a uniform speed and mix at a speed of 1000-2500rpm for 2-10min to obtain a primary coated powder A; Step 2: Place the primary coated powder A at the bottom of a high-speed mixer, take a certain amount of alumina and place it on the upper layer of the primary coated powder A, and mix it in a high-speed mixer at 1000-2500 rpm for 2-10 minutes to obtain a secondary coated powder B; Step 3: placing the secondary coated powder B in a corundum crucible, and transferring it to a high-temperature muffle furnace, heating it to 400-600°C at a certain heating rate and keeping it for 1-5h, then heating it to 1250-1500°C at a certain heating rate and keeping it for 2-6h, after cooling to room temperature, depolymerizing the product in a ball mill for 10-60min to obtain a high-temperature calcined product; Step 4: Place the high-temperature calcined product in a high-speed mixer, take a certain amount of silane coupling agent in an auxiliary material spraying device, spray the auxiliary material at a uniform speed and mix at a speed of 1000-2500rpm for 2-10min to obtain hydrolysis-resistant magnesium oxide for organic silica gel.

[0008] On the basis of the above technical solution, the magnesium oxide in step 1 is dead-burned magnesium oxide with a purity of more than 95%, a median diameter of 5-50 μm, and a maximum particle size of ≤150 μm.

[0009] On the basis of the above technical solution, in step 1, the aluminate is one or more of trimethyl aluminate, triisopropyl aluminate and distearoyloxyisopropyl aluminate, and the added amount is 0.1% to 1% of the mass of magnesium oxide.

[0010] On the basis of the above technical solution, in step 2, the median diameter of the aluminum oxide is 0.1-1 μm, the maximum particle size is ≤2 μm, and the addition amount is 0.5% to 5% of the mass of the magnesium oxide.

[0011] On the basis of the above technical solution, in step three, the heating rate of the high temperature muffle furnace to 400-600°C is 0.5-1°C / min, and the heating rate to 1100-1400°C is 1-3°C / min.

[0012] On the basis of the above technical solution, the ball mill in step three is one of a planetary ball mill, a horizontal intermittent ball mill and a horizontal continuous ball mill.

[0013] On the basis of the above technical solution, the silane coupling agent is one or more of alkyltrimethoxysilane and alkyltriethoxysilane, and the added amount is 0.1% to 0.5% of the high-temperature calcined product.

[0014] Compared with the existing common magnesium oxide, the hydrolysis-resistant magnesium oxide of the present invention has the following advantages: (1) The hydrolysis-resistant magnesium oxide of the present invention is effectively protected by the aluminum oxide coating layer and the silane coupling agent to prevent the magnesium oxide from undergoing a deliquescence reaction in a high temperature and high humidity environment, thereby improving the stability of the magnesium oxide. At the same time, the silane coupling agent coating layer enhances the affinity between the magnesium oxide and the organic silicon matrix, which is beneficial to improving the filling property of the magnesium oxide in the organic silicon matrix, and further improving the thermal conductivity and other comprehensive properties of the organic silicon. (2) The technical process of the present invention is simple, the raw materials are widely available, and the cost is low, which makes it possible to achieve mass production. DETAILED DESCRIPTION

[0015] The embodiments described below specifically illustrate the above contents of the present invention, and particularly illustrate that, based on the principles of the present invention, several adjustments and improvements may be made, and these adjustments and improvements are also considered to be within the protection scope of the embodiments of the present invention.

[0016] The present invention specifically discloses the following specific embodiments:

[0017] Embodiment 1 Step 1: 3 kg of dead-burned magnesium oxide with a median diameter of 5 μm is placed in a high-speed mixer, 5 g of heated and dissolved triisopropyl aluminate is taken into an auxiliary material spraying device, the auxiliary material is sprayed at a uniform speed and mixed at a speed of 1800 rpm for 3 minutes to obtain a primary coated powder A; Step 2: Place the primary coated powder A at the bottom of a high-speed mixer, take 150 g of alumina with a median diameter of 0.5 μm and place it on the upper layer of the coated powder A, and mix it in a high-speed mixer at 2200 rpm for 6 minutes to obtain a secondary coated powder B; Step 3: Place the secondary coated powder B in a corundum crucible, transfer it to a high-temperature muffle furnace, heat it to 500°C at a heating rate of 0.5°C / min and keep it for 2 hours, then heat it to 1400°C at a heating rate of 2°C / min and keep it for 5 hours. After cooling to room temperature, the product is milled and depolymerized in a planetary ball mill at a speed of 500r / min for 20 minutes to obtain a high-temperature calcined product; Step 4: Place 3 kg of the high-temperature calcined product in a high-speed mixer, take 12 g of hexadecyltrimethoxysilane and the auxiliary material spraying device, spray the auxiliary material at a uniform speed and mix at a speed of 2200 rpm for 6 minutes, and finally obtain hydrolysis-resistant magnesium oxide for organic silica gel.

[0018] Embodiment 2 Step 1: 3 kg of dead-burned magnesium oxide with a median diameter of 20 μm is placed in a high-speed mixer, 10 g of heated and dissolved triisopropyl aluminate is taken into an auxiliary material spraying device, the auxiliary material is sprayed at a uniform speed and mixed at a speed of 2000 rpm for 5 minutes to obtain a primary coated powder A; Step 2: Place the primary coated powder A at the bottom of a high-speed mixer, take 100 g of alumina with a median diameter of 0.8 μm and place it on the upper layer of the coated powder A, and mix it in a high-speed mixer at 2000 rpm for 4 minutes to obtain a secondary coated powder B; Step 3: The secondary coated powder B is placed in a corundum crucible, and transferred to a high-temperature muffle furnace, heated to 500°C at a heating rate of 1°C / min and kept warm for 2.5 hours, then heated to 1350°C at a heating rate of 2°C / min and kept warm for 4 hours. After cooling to room temperature, the product is milled and depolymerized in a planetary ball mill at a speed of 500 r / min for 20 minutes to obtain a high-temperature calcined product; Step 4: Place 3 kg of the high-temperature calcined product in a high-speed mixer, take 9 g of dodecyltriethoxysilane and the auxiliary material spraying device, spray the auxiliary material at a uniform speed and mix at a speed of 2000 rpm for 4 minutes, and finally obtain hydrolysis-resistant magnesium oxide for organic silica gel.

[0019] Embodiment 3 Step 1: 3 kg of dead-burned magnesium oxide with a median diameter of 40 μm is placed in a high-speed mixer, 15 g of heated and dissolved triisopropyl aluminate is taken into an auxiliary material spraying device, the auxiliary material is sprayed at a uniform speed and mixed at a speed of 2200 rpm for 8 minutes to obtain a primary coated powder A; Step 2: Place the primary coated powder A at the bottom of a high-speed mixer, take 50 g of alumina with a median diameter of 1 μm and place it on the upper layer of the coated powder A, and mix it in a high-speed mixer at 1800 rpm for 4 minutes to obtain a secondary coated powder B; Step 3: The secondary coated powder B is placed in a corundum crucible, and transferred to a high-temperature muffle furnace, heated to 600°C at a heating rate of 0.5°C / min and kept at this temperature for 3 hours, and then heated to 1300°C at a heating rate of 3°C / min and kept at this temperature for 3 hours. After cooling to room temperature, the product is milled and depolymerized in a planetary ball mill at a speed of 500 r / min for 20 minutes to obtain a high-temperature calcined product; Step 4: Place 3 kg of the high-temperature calcined product in a high-speed mixer, take 9 g of octyltrimethoxysilane and the auxiliary material spraying device, spray the auxiliary material at a uniform speed and mix at a speed of 2000 rpm for 4 minutes, and finally obtain hydrolysis-resistant magnesium oxide for use in organic silica gel.

[0020] Blank Example 1 Blank Example 1 is magnesium oxide without any treatment, which is the magnesium oxide raw material of the embodiment and is dead-burned magnesium oxide with a median diameter of 5 μm.

[0021] Comparative Example 1 Comparative Example 1 is magnesium oxide coated with a silane coupling agent and modified. The method of step 4 of Example 1 is adopted to modify the dead-burned magnesium oxide raw material with a median diameter of 5 μm with a single silane coupling agent. The specific method is as follows: Comparative Example 1: 5 μm modified magnesium oxide: 3 kg of 5 μm dead-burned magnesium oxide was placed in a high-speed mixer, and 12 g of hexadecyltrimethoxysilane was added to the auxiliary material spraying device. The mixture was mixed at a speed of 2200 rpm while spraying the auxiliary material for 6 minutes.

[0022] Comparative Example 2 Comparative Example 2 is a calcined magnesium oxide coated with aluminate once. The method of step 1 and step 3 in Example 1 is adopted to coat and calcine the dead-burned magnesium oxide with a median diameter of 5 μm with aluminate alone. The specific method is as follows: Comparative Example 2: 5μm coated magnesium oxide: 3kg of heavy-burned magnesium oxide with a median diameter of 5μm is placed in a high-speed mixer, 5g of triisopropyl aluminate that has been heated and dissolved is taken in an auxiliary material spraying device, the auxiliary material is sprayed at a uniform speed and mixed at a speed of 1800rpm for 3min to obtain a primary coated powder A; the primary coated powder A is placed in a corundum crucible, and transferred to a high-temperature muffle furnace and heated to 500℃ at a heating rate of 0.5℃ / min and kept warm for 2h, then heated to 1400℃ at a heating rate of 2℃ / min and kept warm for 5h. After cooling to room temperature, the product is depolymerized by ball milling at a speed of 500r / min in a planetary ball mill for 20min to obtain a high-temperature calcined product.

[0023] Comparative Example 3 Comparative Example 3 is a calcined magnesium oxide coated with alumina once. The method of step 2 and step 3 in Example 1 is adopted to coat and calcine the dead-burned magnesium oxide with a median diameter of 5 μm with alumina alone. The specific method is as follows: Comparative Example 3: 5μm coated magnesium oxide: 3kg of dead-burned magnesium oxide with a median diameter of 5μm is placed at the bottom of a high-speed mixer, 150g of alumina with a median diameter of 0.5μm is placed on the upper layer of the dead-burned magnesium oxide raw material, and the high-speed mixer is mixed at 2200rpm for 6min to obtain a primary coated powder B; the primary coated powder B is placed in a corundum crucible, and transferred to a high-temperature muffle furnace and heated to 500℃ at a heating rate of 0.5℃ / min and kept warm for 2h, then heated to 1400℃ at a heating rate of 2℃ / min and kept warm for 5h. After cooling to room temperature, the product is depolymerized by ball milling at a speed of 500r / min in a planetary ball mill for 20min to obtain a high-temperature calcined product.

[0024] Comparative Example 4 Comparative Example 4 is magnesium oxide double coated with aluminate and alumina and calcined. The method of step 1, step 2 and step 3 of Example 1 is used to double-coat and calcine the dead-burned magnesium oxide with a median diameter of 5 μm with aluminate and alumina; the specific method is as follows: Comparative Example 4: 5 μm coated magnesium oxide: 3 kg of dead-burned magnesium oxide with a median diameter of 5 μm was placed in a high-speed mixer, 5 g of heated and dissolved triisopropyl aluminate was taken into an auxiliary material spraying device, the auxiliary material was sprayed at a uniform speed and mixed at a speed of 1800 rpm for 3 minutes to obtain a primary coated powder A; The primary coated powder A was placed at the bottom of a high-speed mixer, 150 g of alumina with a median diameter of 0.5 μm was placed on the upper layer of the modified powder A, and the high-speed mixer was mixed at 2200 rpm for 6 min to obtain the secondary coated powder B; The secondary coated powder B was placed in a corundum crucible and transferred to a high-temperature muffle furnace, heated to 500°C at a heating rate of 0.5°C / min and kept warm for 2 hours, then heated to 1400°C at a heating rate of 2°C / min and kept warm for 5 hours. After cooling to room temperature, the product was depolymerized by ball milling at a speed of 500r / min in a planetary ball mill for 20 minutes to obtain a high-temperature calcined product.

[0025] In order to illustrate the specific application effects of the above examples, the products corresponding to the embodiments and the blank control examples were taken, and the oil absorption value, thermal conductivity, 85°C and 85%RH weathering tests were respectively carried out, and the colloidal state after the weathering test was observed, so as to compare and analyze. The test performance table of magnesium oxide in each embodiment and the blank example is attached below, as shown in Table 1, which shows the actual effect of the hydrolysis-resistant magnesium oxide of the present invention.

[0026] The performance test methods are as follows: 1) Test method for oil absorption value: Use dibutyl phthalate as the oil phase to soak magnesium oxide, ultrasonically disperse the centrifuge tube containing the oil powder sample for a period of time, then centrifuge to pour out the remaining dibutyl phthalate in the centrifuge tube, and invert the centrifuge tube for half an hour to obtain the inorganic powder soaked with oil. During the process, record the mass of the powder and the mass of the remaining dibutyl phthalate, and the oil absorption value of the powder can be calculated. In order to facilitate conversion and comparison, the unit of oil absorption value is set to g / 100g, that is, 100g magnesium oxide can absorb xg dibutyl phthalate; 2) Thermal conductivity test method: The sample is filled with 350cp vinyl silicone oil to a certain ratio (varies with the different oil absorption values ​​of the sample, see Table 1 for details), and stirred at 900r / min for 2min in a vacuum degassing machine to obtain organic silica gel. The thermal conductivity of the organic silica gel is tested using a DRL-Ⅲ thermal conductivity meter. The sample diameter is 20mm, the thickness is 2mm, and the test pressure is 30N. 3) Weathering test at 85℃ and 85%RH: Apply the above-mentioned organic silica gel on a 10cm*10cm glass with a thickness of 0.5mm, and place it horizontally in a constant temperature and humidity oven at 85℃ and 85%RH for a certain period of time. After the weathering period, take it out and observe whether its state is unchanged, cracked, powdered, etc., and retest its thermal conductivity.

[0027] Table 1: Performance test data of blank examples and products prepared in various embodiments

[0028] From the data in Table 1, we can see that: (1) From the comparison of the absorption values, maximum filling ratios and thermal conductivity of Blank Example 1, Comparative Examples 1 to 4 and Examples 1 to 3, it can be seen that the magnesium oxide in Blank Example 1 without any treatment has a lower maximum filling ratio in 350cp vinyl silicone oil, and has poor affinity with the silicone matrix, which cannot give full play to the original advantage of the higher thermal conductivity of magnesium oxide, resulting in a low thermal conductivity in the final test. In Comparative Example 1, the magnesium oxide modified by the silane coupling agent can be seen to have improved oil absorption value, maximum filling ratio and thermal conductivity compared with the untreated magnesium oxide, indicating that the silane coupling agent has modified and coated the magnesium oxide to a certain extent, thereby improving the affinity of magnesium oxide to the silicone matrix. From the comparison of Comparative Examples 2 to 4, it can be found that whether it is magnesium oxide coated once with aluminate, magnesium oxide coated once with alumina, or magnesium oxide coated twice with aluminate and alumina, compared with untreated magnesium oxide, its oil absorption value, maximum filling fraction and thermal conductivity are not greatly improved, but only slightly improved with the deepening of the coating degree, indicating that magnesium oxide coated with aluminate and alumina and calcined cannot effectively improve its affinity in the silicone matrix. It can be seen from the hydrolysis-resistant magnesium oxide of Examples 1 to 3 that, compared with Blank Example 1 and Comparative Examples 1 to 4, the oil absorption value, the maximum filling number and the thermal conductivity are greatly improved, and the performance gap is 2-3 times compared with Blank Example 1, indicating that the dense layer of magnesium-aluminum spinel on the surface of the hydrolysis-resistant magnesium oxide can not only protect the interior of the magnesium oxide from moisture invasion, but also provide more active sites for the silane coupling agent, increase the coverage rate of the silane coupling agent on magnesium oxide, and make the hydrolysis-resistant magnesium oxide more affinity to the silicone matrix, thereby improving the filling performance and thermal conductivity of the hydrolysis-resistant magnesium oxide in silicone gel. (2) From the comparison of the weathering time at 85°C and 85% RH, the state after weathering, and the thermal conductivity after weathering of Blank Example 1, Comparative Examples 1 to 4, and Examples 1 to 3, it can be seen that the magnesium oxide in Blank Example 1, which has not been treated in any way, has poor high-temperature and high-humidity weathering resistance when filled into the silicone matrix. The longest weathering time is only about 30 hours before powdering occurs, and the thermal conductivity cannot be tested again. Moreover, this phenomenon becomes more serious as the particle size becomes smaller. It can be seen from Comparative Example 1 that although the magnesium oxide was initially modified and coated by a silane coupling agent, the affinity of the magnesium oxide to the silicone matrix was improved to a certain extent, so that its oil absorption value, filling number and thermal conductivity performance were improved to a certain extent, but in the 85°C and 85%RH weathering test, it can only remain unchanged for a short time. At the shortest time of 72h, powdering phenomenon has occurred and thermal conductivity cannot be tested, indicating that the coverage rate of the magnesium oxide modified and coated by a silane coupling agent alone is low, and it is unable to prevent moisture in the environment from entering the interior of the magnesium oxide, which eventually leads to the formation of magnesium hydroxide, expansion, cracking, and even powdering. It can be observed from Comparative Examples 2 and 3 that, compared with Blank Example 1, although the 85°C and 85% RH weathering test results of the magnesium oxide calcined by coating with aluminate or alumina once are improved from 16 hours to 100 or 200 hours, the weathering time is still too short for silicone gel, and powdering still occurs after weathering, indicating that the magnesium oxide calcined by coating with aluminate and alumina once has a low coating rate, fails to form a completely coated magnesium-aluminum spinel layer, and fails to completely block the entry of moisture in the environment, resulting in powdering. It can be seen from Comparative Example 4 that the magnesium oxide doubly coated and calcined with aluminate and alumina has greatly improved weathering test results at 85°C and 85% RH compared with Blank Example 1. It can withstand weathering for 450 hours and will not become powdery after weathering. Only the oil absorption value, filling ratio and thermal conductivity performance do not change much, indicating that the magnesium oxide doubly coated and calcined with aluminate and alumina has formed a relatively complete magnesium-aluminum spinel coating layer, which effectively blocks moisture in the environment. However, since it is still a hydrophilic surface and has poor affinity with the silicone matrix, the improvement in oil absorption value, filling ratio and thermal conductivity performance is relatively small. The hydrolysis-resistant magnesium oxide in Examples 1 to 3 performs well under high temperature and high humidity weathering conditions, and its state can remain unchanged for up to 500 hours. After weathering, the thermal conductivity coefficient fluctuates less after retesting, indicating that the magnesium-aluminum spinel on the surface of the hydrolysis-resistant magnesium oxide effectively blocks the entry of moisture in the environment, thereby improving the weathering ability of the hydrolysis-resistant magnesium oxide in a high temperature and high humidity environment, and can provide more active sites for the silane coupling agent, so that it helps magnesium oxide improve its affinity for the silicone matrix while further improving the hydrophobicity of the hydrolysis-resistant magnesium oxide. In summary, it can be observed from the examples that the hydrolysis-resistant magnesium oxide prepared by the present invention exhibits excellent hydrolysis resistance and weathering ability in organic silica gel.

Claims

1. A method for preparing hydrolysis-resistant magnesium oxide for use in organic silica gel, characterized in that: The following steps are involved: Step 1: Place magnesium oxide in a high-speed mixer, take a certain amount of heated and dissolved aluminate in an auxiliary material spraying device, spray the auxiliary material at a uniform speed and mix at a speed of 1000-2500rpm for 2-10min to obtain a primary coated powder A; Step 2: Place the primary coated powder A at the bottom of a high-speed mixer, take a certain amount of alumina and place it on the upper layer of the primary coated powder A, and mix it in a high-speed mixer at 1000-2500 rpm for 2-10 minutes to obtain a secondary coated powder B; Step 3: placing the secondary coated powder B in a corundum crucible, and transferring it to a high-temperature muffle furnace, heating it to 400-600°C at a certain heating rate and keeping it for 1-5h, then heating it to 1250-1500°C at a certain heating rate and keeping it for 2-6h, after cooling to room temperature, depolymerizing the product in a ball mill for 10-60min to obtain a high-temperature calcined product; Step 4: Place the high-temperature calcined product in a high-speed mixer, take a certain amount of silane coupling agent in an auxiliary material spraying device, spray the auxiliary material at a uniform speed and mix at a speed of 1000-2500rpm for 2-10min to obtain hydrolysis-resistant magnesium oxide for organic silica gel.

2. The method for preparing hydrolysis-resistant magnesium oxide for use in organic silica gel according to claim 1, characterized in that: In the step 1, the magnesium oxide is dead-burned magnesium oxide with a purity of more than 95%, a median diameter of 5-50 μm, and a maximum particle size of ≤150 μm.

3. The method for preparing hydrolysis-resistant magnesium oxide for use in organic silica gel according to claim 1, characterized in that: In the step 1, the aluminate is one or more of trimethyl aluminate, triisopropyl aluminate and distearoyloxyisopropyl aluminate, and the added amount is 0.1% to 1% of the mass of magnesium oxide.

4. The method for preparing hydrolysis-resistant magnesium oxide for use in organic silica gel according to claim 1, characterized in that: In the step 2, the median diameter of the aluminum oxide is 0.1-1 μm, and the maximum particle diameter is ≤2 μm; the amount of aluminum oxide added is 0.5% to 5% of the mass of magnesium oxide.

5. The method for preparing hydrolysis-resistant magnesium oxide for use in organic silica gel according to claim 1, characterized in that: In the step 3, the heating rate of the high temperature muffle furnace to 400-600°C is 0.5-1°C / min, and the heating rate of the high temperature muffle furnace to 1100-1400°C is 1-3°C / min.

6. The method for preparing hydrolysis-resistant magnesium oxide for use in organic silica gel according to claim 1, characterized in that: The ball mill in step three is one of a planetary ball mill, a horizontal intermittent ball mill and a horizontal continuous ball mill.

7. The method for preparing hydrolysis-resistant magnesium oxide for use in organic silica gel according to claim 1, characterized in that: In the step 4, the silane coupling agent is one or more of alkyltrimethoxysilane and alkyltriethoxysilane, and the added amount is 0.1% to 0.5% of the mass of the high-temperature calcined product.